On a new species of Ericaella Bonaldo (Araneae, Miturgidae, Eutichurinae), with a cladistic analysis of the genus - Bonaldo, Alexandre B.; Brescovit, Antonio D.; Rheims, Cristina A. (Zootaxa, 2005)
A fourth species of Ericaella, E. florezi n. sp., is described based on males and a female from Cauca, Colombia. A cladistic analysis of all known species of Ericaella, plus two outgroup species (Radulphius camacan Bonaldo and Eutichurus luridus Simon) is presented. The single optimal tree obtained depicted a sister group relationship between Ericaella longipes Chickering plus E. florezi sp. n. and E. samiria Bonaldo plus E. kaxinawa Bonaldo.